Dramatic response of metaplastic breast cancer to chemo-immunotherapy - Sylvia Adams (Nature Portfolio, 2017)
Abstract Frequent overexpression of programmed death-ligand 1 has recently been demonstrated in metaplastic breast cancer, which is a rare breast cancer subtype with limited treatment options. This report describes the clinical course of a patient with metastatic metaplastic breast cancer who had a remarkable response to anti-programmed death-1 therapy with pembrolizumab in combination with nab-paclitaxel. Tissue correlates are presented including tumor-infiltrating lymphocytes and high-programmed death-ligand 1 expression in the tumor.